(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the research is to identify the requirements and obstacles to establishing a university business incubator to develop entrepreneurial ideas among university youth, through a survey of the opinions of a sample of students from the Faculty of Economics at Tishreen University. The research relied on the descriptive analytical approach, and the research community included all the students of the fourth year in the Faculty of Economics at Tishreen University, who numbered (1100) male and female students. As for the research sample, it is a simple random sample that was determined using the statistical sampling law, where the sample size to be drawn was (285) male and female students. A questionnaire was distributed to them, and (263) complete and valid questionnaires were returned for statistical analysis, with a response rate of (92.28%). The results showed that there is a great awareness by the sample members of the requirements and obstacles to the establishment of university business incubators, where the most important requirements are the presence of the incubator in a location close to universities, research centers and industrial zones, the presence of an efficient and effective manager working to manage the incubator in a distinctive way, and following up on the projects it supervises The incubator from the beginning until its independence, and working to coordinate with all parties that work to support the incubator financially, technically, professionally and marketing. While the most important obstacles were: the lack of sufficient financial support, and the lack of highly competitive marketing networks.